Broadly Reactive Influenza Antibodies Are Not Limited by Germinal Center Competition with High-Affinity Antibodies - Rachael Keating; Jenny L. Johnson; David C. Brice; Jocelyn G. Labombarde; Alexander L. Dent; Maureen A. McGargill (mBio, 2020)
ABSTRACT Enhancing the generation of broadly reactive antibodies against influenza A virus (IAV) is a pertinent goal toward developing a universal IAV vaccine. While antibodies that bind conserved IAV epitopes have been identified in humans, antibodies specific for the variable epitopes are much more prevalent than antibodies recognizing conserved epitopes. It is important to define the factors that limit the generation of broadly reactive IAV antibodies in order to develop an effective universal IAV vaccine. The predominant theory is that competition within germinal centers favors the synthesis of high-affinity antibodies specific for the variable region of the virus, and limits antibodies specific for conserved IAV epitopes. Here, we show that reducing germinal center formation and removing competition with high-affinity antibodies was not sufficient to increase broadly reactive IAV antibodies or enhance protection against distinct IAV subtypes. These data disprove the prevailing hypothesis that broadly reactive IAV antibodies are rare due to competition within germinal centers, and reveal the critical need to further investigate factors that limit broadly reactive IAV antibodies. Additionally, our data show that IAV-specific IgM antibodies persist in mice in the absence of germinal centers, highlighting the protective capacity of germinal center-independent IgM antibodies, which are not typically considered when testing correlates of protection, and offer an alternate target for delivering a universal IAV vaccine. IMPORTANCE It is estimated that 250,000 to 650,000 individuals worldwide die each year from seasonal influenza A virus (IAV) infections. Current vaccines provide little protection against newly emerging strains. Thus, considerable effort is focused on enhancing the generation of broadly reactive IAV antibodies in order to develop a universal IAV vaccine. However, broadly reactive IAV antibodies are rare and the factors that limit their generation are not completely understood. Our data disprove the prevailing hypothesis that broadly reactive IAV antibodies are uncommon due to competition in the germinal centers with antibodies specific for the variable, hemagglutinin (HA) head. Understanding the factors that constrain development of antibodies specific for conserved regions of IAV is imperative for developing an effective universal IAV vaccine, which could potentially circumvent a catastrophic pandemic. These findings are significant as they highlight the importance of investigating other mechanisms that contribute to the paucity of broadly reactive IAV antibodies.